2021
DOI: 10.3390/coatings11111354
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Study on the Removal Efficiency and Mechanism of Tetracycline in Water Using Biochar and Magnetic Biochar

Abstract: In this study, a new type of sludge-derived biochar material with high tetracycline removal efficiency, named magnetic Fe3O4 biochar, was accomplished by KOH activated and loaded with magnetic Fe3O4. The particles with spherical pellets observed by SEM, as well as the XRD patterns, indicated that magnetic Fe3O4 nanoparticles were successfully loaded onto the biochar. We studied the adsorption effects and mechanisms of the following three different adsorption materials for tetracycline: biochar (BC), magnetic F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…As the XPS spectra of Fe and O for MBC shows (Figure S2), the Fe2p spectrum exhibited two contributions, i.e., Fe 2+ at 710.1 (27.27%) and Fe 3+ (53.54%) at 712 eV [27]. The ratio of Fe 2+ to Fe 3+ was 0.27:0.54, which was comparable to that in Fe 3 O 4 (0.33:0.67) [28], suggesting the loading of Fe 3 O 4 on MBC.…”
Section: Properties Of Bc and Mbcmentioning
confidence: 94%
“…As the XPS spectra of Fe and O for MBC shows (Figure S2), the Fe2p spectrum exhibited two contributions, i.e., Fe 2+ at 710.1 (27.27%) and Fe 3+ (53.54%) at 712 eV [27]. The ratio of Fe 2+ to Fe 3+ was 0.27:0.54, which was comparable to that in Fe 3 O 4 (0.33:0.67) [28], suggesting the loading of Fe 3 O 4 on MBC.…”
Section: Properties Of Bc and Mbcmentioning
confidence: 94%
“…The change in the values of area, and specific gravity of the carbon, oxygen, and iron confirmed that the aldehydes, Fe-O-Fe, C-O-Fe, CQO/C-O, Fe 2+ , Fe 3+ , Fe 3 O 4 , and FeOOH played a part in the adsorption of TC onto the Fe 3 O 4 modified waste sludge biochar, implying p-p interaction, hydrogen bonding, cation p-interaction and metal ion complexation. 94 The kinetic study revealed that the adsorption of TC onto Fe 3 O 4 /biochar follows the pseudo second order equation. This confirmed that the adsorption of TC was carried out through the chemical mechanism.…”
Section: Adsorptive Mechanism For Tetracycline (Tc)mentioning
confidence: 96%
“…After five cycles of recycling, Fe 3 O 4 modified waste sludge biochar removed 34% TC, which is possibly due to the irreversible impact of some adsorption sites on the surface of the Fe 3 O 4 /biochar. 94…”
Section: Regeneration and Stability Of Bio-based Adsorbentsmentioning
confidence: 99%
“…The main sorption mechanisms of antibiotics include ion exchange, surface complexation, and hydrogen bonding [51]. In previous studies, activated carbon [53], bentonite supported nanoscale Fe/Ni bimetallic particles [54], MCM-41 [55], biochar [56] copolymer/Fe3O4 magnetic nanocomposite [57], MIL-53(Al) metal-organic framework [58], agricultural waste [59], carbon nanotube [60], graphene oxide [61], SiO2 nanoparticles [62] have been used as adsorbent for the water treatment of antibiotics.…”
Section: Treatment Process Of Antibiotics From Wastewatermentioning
confidence: 99%